Modulação da via da quinurenina na malária - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Malaria is still considered a worldwide public health problem. In Brazil, the predominant species is Plasmodium vivax (Pv), responsible for more than 80% of cases. According to published studies, the inappropriate immune response against parasitic infections is considered to be a major driver of the pathogenesis of malaria, and this may be a consequence of a suppressed immune response. Research has shown that indoleamine 2,3-dioxigenase (IDO), an enzyme that converts tryptophan (TRP) to kynurenine (KYN), is driven in part by inflammation and that its high expression plays a key role in the exacerbated increase in KYN. KYN, an immunosuppressive metabolite, binds to AhR transcription factor present in T cells, inducing a higher frequency of regulatory T cells (Tregs) CD4+CD25+FoxP3+ and suppression, anergy and death of effector T cells. However, the role of the KYN pathway in the pathogenesis of malaria has not been fully clarified. For this, the objective of the study is to investigate the functioning of the immune response to high levels of KYN and to demonstrate the influence of this metabolite on the greater expression of Treg cells in vivax malaria. TRP, KYN and pro-inflammatory cytokines were quantified by HPLC and CBA, in patients infected with Pv. To evaluate the expression of Treg cells, the PBMCs of the patients were submitted to immunophenotyping by flow cytometry. In order to understand the activity of IDO in malaria, PBMCs from healthy donors were stimulated in vitro with red cell lysates infected with Pv (iPV-RBC) in the presence or absence of inhibitors of MyD88, enzyme IDO and AhR. In our results, show an increase in KYN levels, AhR expression and increased proliferation of CD4+CD25+FoxP3+ Treg cells. Additionally, these data were accompanied by an increase in proinflammatory cytokines, especially IFN-y which has a positive correlation with the KYN/TRP ratio, in patients with malaria before treatment, compared with patients after treatment, the same it happens in patients who had first malaria episode of compared to individuals with previous malaria. The higher frequency of Treg cells is accompanied by higher expression of AhR and proliferation in this cell population. Likewise, when evaluating in vitro, KYN levels remained high with greater expression of Treg cells, when we inhibited IDO or AhR the frequency of Treg cells decreased. Thus, our data reinforce that Treg cells are more expressed in malaria and that this increase may be related to KYN activity when it binds to the AhR transcription factor.
Keywords: Malária - Tratamento; Epidemiologia - Pesquisa; CIENCIAS BIOLOGICAS: IMUNOLOGIA; Malária; Indoleamina 2,3 – dioxigenase; Triptofano; Quinurenina; Células T reguladoras